Misdiagnosis of renal pelvic unicentric Castleman disease: a case report - Fu, Dian; Yang, Bo; Yang, Ming; Xu, Zhenyu; Cheng, Wen; Liu, Zhijia; Zhang, Liming; Mao, Zhiguo; Xue, Cheng (Frontiers in Surgery, 2023)
Castleman disease is a rare heterogeneous lymphoproliferative disorder of unknown etiology.Unicentric Castleman disease (UCD) is more common. UCD can occur at any site where lymphatic tissue exists, most commonly in the mediastinum, neck, and abdominal cavity, etc. in the current study, we reported a 46-year-old woman, who has left low back pain and discomfort. Magnetic resonance imaging (MRI) of the kidneys showed the left renal pelvis was occupied, left hydronephrosis, and the left renal hilum and retroperitoneal lymph nodes were enlarged. Enhanced kidney CT showed that the 'pelvic tumor' was moderately enhanced in the bottom part in corticomedullary phase, while in nephrogenic phase, it was unevenly enhanced with a highly enhanced bottom part and weakly enhanced upper part.In excretory phase, reinforcement was decreased. "left renal pelvis tumor" was diagnosed and she underwent surgical treatment with left nephrectomy. However, histopathological examination indicated the UCD. We suggest that for renal pelvic tumors having imaging characteristics of homogeneous soft tissue density and heterogeneous CT enhancement, the hyaline vascular type of UCD could be taken into consideration for differential diagnosis.